The frontier factor in the formation of the hero's image in Russian society - Mariia A. Podlesnaia; Oleg K. Shevchenko (Наука. Культура. Общество)
The article examines the concept of a hero in relation to the concept of a frontier, which the authors understand as a "contact field", a boundary that connects rather than separates the spatio-temporal field of conjugation of two or more realities. Particular attention is paid to the development of the frontier as a point of assembly and the personality of the hero and the new social normality. The need for a comparative analysis of the concepts of subject, actor, and hero that already exist in sociology is indicated. An attempt is made to differentiate these concepts, the main features of the hero as a total subject are given, the importance of distinguishing between an everyday hero and a "frontier" hero is indicated. The influence of the frontier as a factor in the formation of the hero's image is substantiated based on the materials of an empirical study conducted by the authors of the article in eight Federal Districts of the Russian Federation in 2023 (n = 1350). For this purpose, data are analyzed on a number of open and semi-closed questions depending on the place of residence of the respondents, that is, the territorial factor. The authors of the article come to the conclusion that the length of Russia and the diversity of its regions, the frontier status of some of them, provide the corresponding specificity and demand for a hero. Respondents from those subjects of the Russian Federation that currently act as a frontier themselves articulate their idea of a hero and heroism much more clearly. The military hero remains the textbook hero for Russians. A significant part of the independently named heroes are outstanding personalities, primarily of the Soviet era, mainly military leaders, politicians, child heroes of the Great Patriotic War. Everyday workers and laborers - doctors, health workers, volunteers, rescuers, teachers, scientists, etc., which was typical for the Soviet era, are not currently singled out as heroes by respondents. Which leads to the conclusion that the actor of Soviet modernism, which was associated with heroism, was closely associated with the concept of a hero (in particular, labor), is not relevant in the minds of Russians today. Such transformations are associated by the authors with the influence of the situational factor, as well as with the change of the corresponding social ontologies.